Literature in the digital age: An investigation of technological influences - Usmani, Saima; Ali, Elsadig Hussein Fadlalla; Kottaparamban, Musadhique Kottaparamban; Ahmed, Fawzi Eltayeb Yousuf Ahmed; Hamd, Muna Abdalatif Abbass; Ibrahim, Mohammed Ali El-Siddig (Research Journal in Advanced Humanities, 2025)
Digitalization has created new opportunities for various industries, including the literary industry. Different trends are gradually impacting the book industry, from the readers' choice to the mode of publishing. Among these trends, the most significant one, which has been neglected as a study topic in recent cases, is the change in writing styles and the invisible fusion of different subgenres, regardless of their main ideas. This study has focused on developing an understanding of the changes in perspectives from both writers and readers regarding e-books compared to traditional printed books. Based on the analysis, a methodological approach for conducting a secondary qualitative review of literature depending on the systematic review mechanism is used; numerous studies published in Google Scholar regarding the same topic between 2020 and the current year are evaluated, and 15 such studies have been chosen for analysis. Their thorough study has raised the view that the emergence of self-publishing and the invisible fusion of subgenres such as science fiction with thriller and love stories are not diminishing the popularity of printed books, but rather, e-books are becoming increasingly prevalent alongside them.